Incidence and farmers' knowledge of aflatoxin contamination and control in Eastern Democratic Republic of Congo. Issue 6 (16th July 2018) - Udomkun, Patchimaporn; Wossen, Tesfamicheal; Nabahungu, Nsharwasi L.; Mutegi, Charity; Vanlauwe, Bernard; Bandyopadhyay, Ranajit
Abstract: Despite efforts to reduce aflatoxin contamination and associated mycotoxin poisoning, the phenomenon continues to pose a public health threat in food and feed commodity chains. In this study, 300 samples of cassava, maize, and groundnut were collected from farmers' households in Eastern DRC and analyzed for incidence of aflatoxins. In addition, the farmers' level of knowledge of the causes and consequences of contamination and the measures for prevention were also examined by administering questionnaires to a cross section of 150 farmers. The results showed the presence of aflatoxins in all samples, with levels ranging from 1.6 to 2, 270 μg/kg. In 68% of all samples, total aflatoxin contamination was above 4 μg/kg, the maximum tolerable level set by the European Union. Farmers ranked high humidity, improper storage practices, and poor soils as potential causes of aflatoxin contamination and changes in color, smell, and taste, and difficulty in selling crops as consequences. They identified crop management practices as the most effective way to control contamination. The results also revealed that most farmers apply preharvest crop management practices as a means of controlling contamination. More educated households were more knowledgeable about aflatoxins. Female‐headed and married households were less likely to be willing to pay for aflatoxin control. About 28% of farmers claimed to be willing to allocate resources to seed intervention while a smaller proportion agreed to pay for training and information services. The result further suggests that an adoption of pre‐ and postharvest technologies together with awareness creation is still required to reduce aflatoxin contamination in the country. Abstract : Cassava, maize, and groundnut samples were 100% positive for aflatoxin. Kendal's concordance was used to rank the causes and consequences of aflatoxin contamination, and measures for prevention. Congolese farmers' knowledge and awareness of aflatoxin control, and their willingness to pay for it was influenced by socioeconomic characteristics. A small number claimed to be willing to allocate resources to aflatoxin control interventions.